New Plants for Florida: Varieties Produced by the Florida Agricultural Experiment Station--Table of Contents - Richard L. Jones; Mary Duryea; Berry J. Treat (EDIS, 2003)
This document is part of Circular 1440, a publication of the Florida Agricultural Experiment Station, the Agronomy Department and IFAS Communication Services, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Publication date August 2003. Originally published as a booklet by IFAS Communication Services June 2003.